Corrosion– Major Cause of Deterioration of Reinforced concrete - Sanjeev Kumar Verma (AG Volumes, 2022)
Corrosion of reinforced bars in reinforced concrete structures is the main cause of structural deterioration of bridge decks, tall buildings, tunnels and reinforced containers. In order to evaluate the service life of reinforced concrete structures, the mechanisms of corrosion of steel in concrete must be assessed and modelled. The present work deals with a literature review on corrosion mechanisms happening during the life of a reinforced concrete structure. Usually, the deterioration process begins with the “passive state” of the steel, when aggressive reagents - mainly chloride and carbon dioxide, responsible for a pH decrease onto the steel-concrete interface - are penetrating inside the porous concrete.